A new subspecies of Evergestis kopetdagensis Kuznetzov, 1958 (Lepidoptera: Pyralidae) from Kyrgyzstan and Tajikistan - S.K. Korb (Russian Academy of Science. Southern Scientific Centre. Federal Research Centre, 2018)
A new subspecies Evergestis kopetdagensis sinevi Korb, subsp. n. (type locality: Kyrgyzstan, Bishkek environs, near Ala-Too settlement, 42°47ʹ33.00ʺ  N, 74°41ʹ38.36ʺ  E, 982  m) is described from Kyrgyzstan and Tajikistan. This new subspecies differs from the nominotypical one by the habitus (it is darker and has more contrast wing pattern), male genitalia (especially by the narrow valvae in its middle part) and by bionomics. Differential diagnosis of Evergestis kopetdagensis sinevi Korb,  subsp.  n. Wing pattern differences are the following: nominotypical subspecies with little bit brilliant ground colour when in the new subspecies it is mat; the nominotypical subspecies is much lighter than the new one; pattern lines on the forewing upperside are darkolive-grey and complete in the new subspecies when these lines in E.  kopetdagensis kopetdagensis are light-brown and incomplete; on the hindwing upperside margin in the nominotypical subspecies the dark intermittent line is present which is not present in the new subspecies. The new subspecies antennae is the same color as wings ground color, in the nominotypical subspecies these structures are darker than wings ground color. Male genitalia differences: in E.  kopetdagensis kopetdagensis the valvae sides are almost parallel when in the new subspecies they are clearly narrowed in its middle part; in the new subspecies the subuncus has no spikes when in the nominotypical subspecies the subuncus has it. Ecological differences: according to Kusnetzov (see References) in Kopet Dagh the nominotypical subspecies inhabits shallow forests in the lower part of the forest zone while a new subspecies was collected in Kyrgyzstan and Tajikistan in low-altitudinal steppe exclusively.